Understanding the Distribution of Candida auris and Its Antifungal Susceptibility in Diverse Samples - Singh, Dr Puneeta; Malik, Dr Shalabh; Lal, Vandana (International Journal of Innovative Research in Medical Science, 2024)
Background: This study aims to assess the prevalence and susceptibility to antifungal drugs of Candida auris, a pathogen known for causing both invasive and noninvasive infections associated with high mortality rates. This yeast, classified as an emergent superbug fungal pathogen, has garnered global attention due to its resistance to azole antifungal agents. Variations in susceptibility patterns underscore the need for heightened awareness and systematic surveillance efforts. Results: Over 4 years, there were 8,351 (41.5%) reported cases of Candida infections, including 268 (3.2%) attributed to C. auris, identified across various clinical samples such as respiratory (45.9%), urine (23.8%), blood (11.9%), sterile body fluids (8.2%), pus (6.7%), and tissue (3.3%). In Delhi, Candida auris, an emerging infection, predominantly affected respiratory samples like BAL (66), endotracheal tip (32), and sputum (25), totalling 268 (3.2%) positive isolates, with a higher incidence observed in males (64.5% male vs. 35.5% female). This study emphasizes the notable sensitivity of Caspofungin and Micafungin against C. auris isolates, alongside the concerning development of high-level resistance to Azoles and Amphotericin B in clinical settings in North India. Conclusion: In conclusion, the emergence of multidrug-resistant (MDR) C. auris poses significant challenges in treatment of invasive candidiasis, drawing significant concern from policymakers and underscoring the urgent need for stringent antifungal prescription policies. Echinocandins remain pivotal in the treatment of C. auris infections, proving highly effective despite increasing resistance to other antifungal classes. This study aims to raise public awareness, effective management strategies about C. auris, advocate for increasing knowledge and vigilance among physicians and healthcare workers, especially in critical care settings, to monitor resistance patterns and the development of straightforward, rapid, accurate, and cost-effective diagnostic methods, and promote future research, including whole genome analysis.